The need for developing Canva-based interactive learning media to improve students’ literacy abilities - Fitri, Putri Intan Mutiara; Efendi, Raimon (PT The Collaboration UVW, 2024)
This research aimed to analyze the need for developing Canva-based learning media to improve the literacy skills of Phase B students at Public Elementary School. The problems faced in the field are students’ lack of literacy skills to understand and reason, students are not enthusiastic when asked to read, after reading students cannot understand the content that they have read so they are unable to retell the content of the reading, and students appear less interested when asked. to read using a reading textbook. These problems underlie this development need analysis research. This research used a non-associative quantitative analysis research methodology. The research sample consisted of 52 people from 110 populations. The results of this development need analysis research recommend that it is necessary to develop Canva-based interactive learning media to improve students’ literacy skills.